Closing the Gender Gap in Salary Increases: Evidence from a Field Experiment on Promoting Pay Equity - Jakob Alfitian; Marvin Deversi; Dirk Sliwka (Institute of Labor Economics (IZA), 2023)
We present a natural field experiment on promoting pay equity through simple modifications to the salary review process involving 623 middle managers and 8,951 subordinate employees of a large technology firm. We first document a gender gap not only in salary levels but also in salary increases. Our treatments provide for a gender-blind reallocation of the salary increase budget available to middle managers aimed at promoting pay equity, along with different variants of a corresponding decision guidance. We show that the budget reallocation combined with an explicit decision guidance, while still leaving middle managers discretion in allocating the budget, can completely eliminate the gender gap in salary increases. The treatments also do not appear to undermine the desired performance differentiation in salary increases. We thus show that simple modifications to the salary review process can go a long way toward achieving pay equity by preventing gender gaps from widening throughout employees' careers.
Keywords: J31; J71; M52; 330; gender pay gap; pay equity; randomized controlled trial; salary structure